FAKTOR-FAKTOR PENENTU MUSLIM MILENIAL BERINSVESTASI DI TABUNGAN EMAS SYARIAH: (DETERMINANTS OF MILLENNIAL MUSLIMS' INTEREST IN INVESTING IN SHARIA GOLD SAVINGS) - Salama, Sri Cahyaning Umi; Wardani, Mahdayusiska; Hakim, Imamul (UPT Penerbitan Universitas Jember, 2024)
The purpose of this study was to determine the factors that influence the interest of millennial Muslims to invest in sharia gold savings in Malang City. The population in this study were those who were included in the millennial generation with a birth range of 1980 to 2000 in Malang City. The sampling technique used the accidental sampling method with a total of 100 respondents. The data source in this study was primary data. Data collection was carried out by distributing questionnaires via Google Form. The data analysis technique, namely SEM or Structural Equation Model modeling, was used as a research data processing technique with the help of the SmartPLS 4.0 test tool. The results of this study indicate that: (1) the knowledge factor has a significant effect on the interest in investing in sharia gold savings, (2) the security factor does not have a significant effect on the interest in investing in sharia gold savings (3) the investment risk perception factor has a significant effect on the interest in investing in sharia gold savings.